2010
DOI: 10.21091/mppa.2010.3023
|View full text |Cite
|
Sign up to set email alerts
|

Validating a Dance-specific Screening Test for Balance: Preliminary Results from Multisite Testing

Abstract: Few dance-specific screening tools adequately capture balance. The aim of this study was to administer and modify the Star Excursion Balance Test (oSEBT) to examine its utility as a balance screen for dancers. The oSEBT involves standing on one leg while lightly targeting with the opposite foot to the farthest distance along eight spokes of a star-shaped grid. This task simulates dance in the spatial pattern and movement quality of the gesturing limb. The oSEBT was validated for distance on athletes with hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 13 publications
1
65
0
Order By: Relevance
“…Dynamic postural control assessments are used in the athletic setting in an attempt to quantify functional postural control performance through the Star Excursion Balance Test (SEBT), the Lower Quarter Y-Balance Test (YBT), and gait stability. 21,[33][34][35][36][37][38][39][40][41][42][43][44][92][93][94][95][96][97][98] The SEBT and YBT have helped identify lower extremity musculoskeletal injury risk and balance deficits of athletes by measuring single leg stance postural control while executing multidirectional reaches with the non-stance leg 17,92,[99][100][101][102] while gait analysis has helped identify more conservative gait strategies 34,35,39,40,[103][104][105] and postural control deficits of individuals following concussion. 21,34,103,104 The YBT assesses dynamic postural control performance of single leg stance while simultaneously reaching the non-stance limb in three of the six directions used in the SEBT: anterior, posteromedial, and posterolateral.…”
Section: Dynamic Postural Control Assessmentsmentioning
confidence: 99%
“…Dynamic postural control assessments are used in the athletic setting in an attempt to quantify functional postural control performance through the Star Excursion Balance Test (SEBT), the Lower Quarter Y-Balance Test (YBT), and gait stability. 21,[33][34][35][36][37][38][39][40][41][42][43][44][92][93][94][95][96][97][98] The SEBT and YBT have helped identify lower extremity musculoskeletal injury risk and balance deficits of athletes by measuring single leg stance postural control while executing multidirectional reaches with the non-stance leg 17,92,[99][100][101][102] while gait analysis has helped identify more conservative gait strategies 34,35,39,40,[103][104][105] and postural control deficits of individuals following concussion. 21,34,103,104 The YBT assesses dynamic postural control performance of single leg stance while simultaneously reaching the non-stance limb in three of the six directions used in the SEBT: anterior, posteromedial, and posterolateral.…”
Section: Dynamic Postural Control Assessmentsmentioning
confidence: 99%
“…Overall, the selected studies demonstrated a variety of testing procedures (Tables 1-3): 24 used force plates as the principal apparatus for testing balance 14,15,17,20,34-37,39,53-56,60,63-70,73,74 , 10 studies employed motion capture analysis 41,[52][53][54]59,61,62,[64][65][66] , seven studies used the stabilometer, sometimes referred to as a "seesaw" 16,18,19,33,38,75 , placed on a force plate 36 , five studies utilised a pressure mat 13,30,31,40,71 , four studies included the SEBT or modified versions: SEBT 31,44,76 , the modified SEBT 76 , the Y-balance (SEBT components) 72 . Other assessment tools included the Balance Error Scoring System (BESS) 44 , the modified Bass Test of Dynamic Balance (BASS) 44 , a goniometer and computer generated visual target 42 , a Rod and Frame Test (RFT) 16 , a Biodex System 77 , a Foam and Dome Test 45 , and an observed timed-measure 51 .…”
Section: Testing Proceduresmentioning
confidence: 99%
“…The validity and reliability of balance tests for dancers remains a largely unresearched area. Modifications to the Star Excursion Balance Test have been investigated by only two studies with the aim to examine its potential use as a dance-specific balance screening tool 76,84 . Balance research using dance-specific pirouettes has been undertaken 55,62,65,66,68,78 but its validity as a balance tool is still under debate due to the variety of test conditions, and small sample sizes.…”
Section: Balance Training and Balance Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gray developed this test as a rehabilitative tool and then it becomes a clinical use for athletic and pathologic populations [1]. It covers a range of fields including screening [2,3], injury identification [4,5], training and rehabilitation [6,7,8]. The Star Excursion Balance Test needs to perform how far they can reach without overbalance.…”
Section: Introductionmentioning
confidence: 99%